The Influence of Traditional Navigation Knowledge and the Utilization of Ethnomathematics on the Success of Traditional Fishermen's Operations - Kurniawan, Dwi Agus; Elfaituri, Khaled; Samuel, Ahenkora; Dalhadi, Nehmar J.; Sindu, Sindu (Interval: Indonesian Journal of Mathematical Education, 2023)
Purpose of the study: This study aims to analyze the influence of traditional navigation knowledge and the use of ethnomathematics on the success of traditional fishermen's operations in Indonesia. Using a quantitative approach and the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The survey was conducted on traditional fishermen who have been operating for more than five years, utilizing local navigation knowledge, and applying mathematical principles in going to sea.Methodology: The research instrument was a closed questionnaire with a 5-point Likert scale to measure three main variables: Traditional Navigation Knowledge, Utilization of Ethnomathematics, and Success of Traditional Fishermen's Operations. Data were analyzed through validity, reliability, and structural model tests.Main Findings:  results show that traditional navigation knowledge has a significant effect on the success of fishermen's operations with a path coefficient of 0.45 (p = 0.002). The use of ethnomathematics also has a significant effect with a path coefficient of 0.36 (p = 0.005). Overall, the two independent variables explain 60% of the variation in the success of fishermen's operations. This finding emphasizes the importance of integrating local wisdom and scientific approaches to improve the effectiveness and efficiency of traditional fishermen's activities.Novelty/Originality of this study: This research has a novelty by integrating two approaches, namely the influence of traditional navigation knowledge and ethnomathematics, and exploring mathematical concepts in local culture. The results provide an important contribution in developing a model that combines local wisdom and scientific principles to support the sustainability of traditional fishermen's operations in Indonesia.